E-Deposit in Academic Use - Ajanovski, Vangel; Gushev, Marjan; Antovski, Ljupco (SRCE-Sveučilišni računski centar, 2002)
The e-Deposit is a deposit that can be managed in electronic form. The concept of a fund accessible for different financial transactions makes the e-Deposit appropriate for use at universities. The application is implemented in three-tier architecture. Because of the extensive exchange of financial data over the internet, the data integrity is secured. The business and data access tier are implemented in a modular manner helping the robustness of the application and reducing the risk of unwanted behavior. Spe cial modules are used, that enable the integra tion of an e-commerce scenario in an already ex isting university information system.
Keywords: e-Deposit, SSL, PKI, e-commerce, e-business, e-university, certificates, encryption, XML, database